Answer:
The given expression represents the Associative Property of Addition.
Explanation:
Here, the given expression is given as:
(2+3.4) + 6 = 2 + (3.4+6)
Now, for any 3 terms a, b and c the given properties in the options are described as:
1. Associative Property of Addition
(a +b) + c = a + (b + c)
2. Commutative Property of Multiplication
a x b = b x a
3. Inverse Property of Multiplication
4. Commutative Property of Addition
a+ b = b + a
Hence, from the given expression,we can see that:
(2+3.4) + 6 = 2 + (3.4+6)
⇒(a +b) + c = a + (b + c)
Hence, the expression represents the Associative Property of Addition